Fine structural analysis on triad spinning spigots of an orb‐web spider's capture threads. Issue 3 (19th June 2014) - Park, Jong‐Gu; Moon, Myung‐Jin
Abstract Capture threads of the golden orb‐web spider Nephila clavata are produced from the silks of a pair of triad spinning units composed of a flagelliform gland (FLG) and two aggregate glands (AGG). In N. clavata, arrangement of the triad spigots is closely related to coating an axial supporting fiber with sticky aqueous droplets on a continuous and consistent basis for capture thread production. The central spigot of FLG and peripherally located AGG spigots are aligned along a single plane, and both have bullet‐type spigots with flexible segments. In particular, the pear‐shaped spigot of the AGG with a wide‐aperture nozzle provides not only sufficient luminal space for controlling transient storage of the aqueous gluey substance but also an effective spatial system that thoroughly coats the axial fibers with a viscous aqueous solution.